PERAN GENERAZI Z DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DENGAN KEJADIAN PENYAKIT - Azizah, R.; Winarko, Edi; Kusumawati, Mifaidah; Martini, Santi; Sulistyorini, Lilis; Aaqilah Salsabila, Zaneta; Naura, Nuha (Dian Nuswantoro Semarang, 2024)
The environment, both biotic and abiotic factors influence and are influenced by humans. One of the factors that affect the environment is the problem of waste management, because pollution due to waste that is not managed properly can have a negative impact on health by causing various diseases. Generation Z is able to have great characteristics and potential to improve their environment which has been damaged by individuals who do not want to protect their own environment.This research aims to raise awareness of generation Z in managing household waste regarding diseases caused by waste. This type of research is a quantitative research with the design of this research is associative causal which has the aim of looking for causal relationships between variables. The target in this study were the people in RW 9 Larangan Village, Candi District, Sidoarjo Regency with a total population of 70 people.The conclusion in this study is that only household waste management has a significant relationship with a negative relationship to diseases caused by waste. So the advice that can be given based on the results of this study is that people should be more aware of risk factors household waste management.